Acute cytomegalovirus hepatitis in an elderly patient: A case report (Research, Society and Development, 2025)
Introduction: Cytomegalovirus (CMV), also known as human herpesvirus type 5, is transmitted through body fluids and can infect a large number of cells in the individual, enabling systemic transmission within the host. This virus generally causes asymptomatic infections in immunocompetent individuals or mononucleosis-like syndrome, but it can rarely cause systemic infections, such as hepatic manifestation. Objective: This article aims to report a case of hepatitis associated with cytomegalovirus, reinforcing the importance of this agent in the differential diagnosis of acute hepatitis. Methodology: elaborate review of the patient's medical records, as well as a literature review on the subject, indicating epidemiology, pathogenesis, clinical manifestations, diagnosis and treatment. Related to the case: A 60-year-old female patient required care at na care at an emergency room with complaints of malaise, asthenia and fever. Antibiotic therapy was prescribed, without remission of symptoms. Blood count showed low hematocrit levels and red blood cells in Rouleaux. Patient with hypertension, dyslipidemia, ex-smoker and immunocompetent. The patient required hospitalization due to anemia, hepatomegaly and positive IgM and IgG serology for CMV, in addition to an upper abdominal ultrasound showing increased parenchyma. After 10 days of hospitalization, there were no relevant complications, and the case was confirmed as cytomegalovirus hepatitis after a positive viral load (quantitative CMV PCR of 9,770 IU/mL). Conclusion: We highlight the manifestation of cytomegalovirus infection presenting with hepatitis in immunocompetent elderly individuals, demonstrating the importance of analyzing this virus in the differential diagnosis of acute hepatitis and encouraging the exploration of knowledge about this disease.